Heart failure on peritoneal dialysis: Where do we stand? - Reis,Marina (2021)
ABSTRACT Cardiovascular disease continues to be the most frequent cause of death in peritoneal dialysis patients and an important obstacle for the improvement of technique survival. Heart failure diagnosis and management is particularly challenging among dialysis patients, and this condition remains underdiagnosed and undertreated in this population. The most common phenotype of heart failure among peritoneal dialysis patients is heart failure with preserved ejection fraction, diastolic disfunction and left ventricular hypertrophy. Unfortunately, unlike what happens with heart failure with reduced ejection fraction, there is lack of evidence to support a specific drug regimen to treat heart failure with preserved ejection fraction. Several conditions associated with end stage kidney disease, such as anemia, hyperphosphatemia, secondary hyperparathyroidism, inflammation, and insulin resistance seem to be involved in the pathogenesis of heart failure with preserved ejection fraction and for this reason, the term uremic cardiomyopathy has been proposed. There is a lack of evidence regarding the optimal heart failure treatment for peritoneal dialysis patients and more studies are needed to assess the efficacy and safety of the new drugs available for heart failure treatment. This review explores the spectrum of heart failure on peritoneal dialysis, its pathogenesis, risk factors and possible therapeutic and preventive measures.